Development and Validation of the Scale for Analysing the Consumption Behaviours of E-Sports Players Using a Mixed-Methods Approach - Oguzhan Gul; Zuhal Yurtsizoglu (SAGE Open)
This paper aims to develop the E-Sports Consumption Behaviour Assessment Scale (E-CBAs) to assess consumption trends among e-sports consumers, addressing the economic and social dimensions of the digital gaming industry. With the rapid growth of digital games and the rising popularity of e-sports, the E-CBAs was developed to capture three consumption dimensions: hedonic, utilitarian, and luxury. Qualitative data were gathered through in-depth interviews with 12 professional e-sports players, while quantitative data were collected from 314 e-sports players using the newly developed E-CBAs. The findings reveal that digital games strengthen social bonds and enhance problem-solving and strategic thinking skills. Economically, the in-game spending of e-sports players significantly contributes to industry growth. This paper provides a comprehensive evaluation to support strategic decision-making in the digital gaming sector, highlighting the E-CBAs as a valuable assessment instrument for future research and applications.